The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Roy, Helen E.; Brown, Peter M. J.; Adriaens, Tim; Berkvens, Nick; Borges, Isabel; Clusella-Trullas, Susana; Comont, Richard F.; De Clercq, Patrick; Eschen, Rene; Estoup, Arnaud; Evans, Edward W.; Facon, Benoit; et al. (Biological invasions, 2016)
The harlequin ladybird, Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), is native to Asia but has been intentionally introduced to many countries as a biological control agent of pest insects. In numerous countries, however, it has been introduced unintentionally. The dramatic spread of H. axyridis within many countries has been met with considerable trepidation. It is a generalist top predator, able to thrive in many habitats and across wide climatic conditions. It poses a threat to biodiversity, particularly aphidophagous insects, through competition and predation, and in many countries adverse effects have been reported on other species, particularly coccinellids. However, the patterns are not consistent around the world and seem to be affected by many factors including landscape and climate. Research on H. axyridis has provided detailed insights into invasion biology from broad patterns and processes to approaches in surveillance and monitoring. An impressive number of studies on this alien species have provided mechanistic evidence alongside models explaining large-scale patterns and processes. The involvement of citizens in monitoring this species in a number of countries around the world is inspiring and has provided data on scales that would be otherwise unachievable. Harmonia axyridis has successfully been used as a model invasive alien species and has been the inspiration for global collaborations at various scales. There is considerable scope to expand the research and associated collaborations, particularly to increase the breadth of parallel studies conducted in the native and invaded regions. Indeed a qualitative comparison of biological traits across the native and invaded range suggests that there are differences which ultimately could influence the population dynamics of this invader. Here we provide an overview of the invasion history and ecology of H. axyridis globally with consideration of future research perspectives. We reflect broadly on the contributions of such research to our understanding of invasion biology while also informing policy and people.